2011
DOI: 10.1016/j.biosystemseng.2011.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of chicory seeds maturity by chlorophyll fluorescence imaging

Abstract: Chicory (Cichorium intybus L.) seed production includes sorting to remove foreign materials and non-viable seeds. A machine vision system was developed to monitor the fluorescence in order to detect the immature chicory seeds. It comprised a monochromatic light source, a highpass filter and a monochromatic CCD camera sensitive to red and infrared. With this device, blue light reflected by the seeds was blocked whilst red fluorescence was measured by the camera. A segmentation algorithm was designed to estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 14 publications
0
11
0
2
Order By: Relevance
“…Chlorophyll fluorescence-based technology is centered on the capacity of chlorophyll, which is often present in seeds during their development to emit light in a slightly longer wavelength in relation to the light that was absorbed (Misra et al, 2012;Smolikova et al, 2017). Because chlorophyll degradation is usually observed at late steps of seed maturation (Smolikova et al, 2020), chlorophyll content and its fluorescence are inversely proportional to the seed maturity and, consequently, to its quality (Ooms and Destain, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Chlorophyll fluorescence-based technology is centered on the capacity of chlorophyll, which is often present in seeds during their development to emit light in a slightly longer wavelength in relation to the light that was absorbed (Misra et al, 2012;Smolikova et al, 2017). Because chlorophyll degradation is usually observed at late steps of seed maturation (Smolikova et al, 2020), chlorophyll content and its fluorescence are inversely proportional to the seed maturity and, consequently, to its quality (Ooms and Destain, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Although it has already been demonstrated that the chlorophyll fluorescence induction can be used to predict the maturity stage of mango [14], papaya fruit [15], lemons [16] and chicory seeds [17]. Our study proved that an accurate classification of tomato fruit according to the maturity stage could be achieved by using chlorophyll fluorescence induction.…”
Section: Resultsmentioning
confidence: 58%
“…CF analysis of seeds of Brassica oleracea L. showed that germination increased as CF decreased (Jalink et al , 1998a, b). Ooms and Destain (2011) showed a similar relationship for chicory ( Cicorium intybus L.). CF analysis is now used to improve overall seed lot quality for a range of species, by removing individual seeds that are less mature (Nijënstein, 2014 and references therein).…”
Section: Introductionmentioning
confidence: 80%